Ensino jurídico: história, currículo e interdisciplinaridade - Mossini, Daniela Emmerich de Souza (2010)
This present study has the aim to examine the new demands that the Brazilian juridical teaching tries to fulfill helped by the historical knowledge of public policies responsible for the construction of the national Juridical Teaching curriculum, emphasizing Portugal influence on it. Based on the philosophical and historical perspectives since the creation of Law Courses (1827) until the present days, searching for a combination of Studies in the Curriculum Area with Law, discussing the historical intervention articulated of the public and private in the construction of its paradigms and reach the interdisciplinarity. To the elaboration of this study, we are going through an itinerary that begins with a brief overview of today s juridical teaching, a history about the Juridical Teaching, besides a history about the theories of Curriculum, Juridical Teaching, the international influences and the search for innovation. The most specific exam is about the understanding that the current problems are due to the lack of historical knowledge about the Portuguese legacy concerning the Juridical Teaching, and also the lack of distinction about the theoretical fundaments to a good curricular organization of the undergraduate courses in the perspective of an organic link between the Juridical Teaching and the social and political development of the country. The methodological option used was the qualitative research, from the bibliographical type. The objective of this research is to approach the historical trajectory of the Law courses in Brazil focusing the interference, the influence, and the heritage received from the Law courses form Portugal with the goal to promote a contextualized reflection about the needs for a change in the public and private intervention in the formation of the candidates to become bachelor of Laws. In this sense, it is necessary a critical look and thought, so that we can evaluate and plan the formation guidelines that enforce and charge to all that are committed, that is, to educate professionals that, beyond the ability to deal and research the juridical knowledge with autonomy, have the ethics comprehension of his/her professional activity articulated to the interdisciplinary humanistic knowledge searching for an effective social participation. It is concluded that the great change is found in the construction of a new conception about the juridical teaching that serves the social demands and get the innovation to graduate professionals with a perception of new ways to work in the juridical area